Recent observations of high mass density polar mesospheric clouds: A link to space traffic?. Issue 11 (6th June 2013) - Siskind, David E.; Stevens, Michael H.; Hervig, Mark E.; Randall, Cora E.
Abstract [1] Observations of polar mesospheric clouds by the Aeronomy of Ice in the Mesosphere Explorer show that for the Northern summers of 2007–2010, the cloud ice water content (IWC) and occurrence frequency varied with the meteorological forcing from the Southern winter stratosphere. With the increase in solar flux in the last two years, expectations were that the clouds would decrease due to reduced water vapor (H2O) and/or higher temperatures. Surprisingly, we observe more clouds in 2011 and 40% greater IWC in 2011 and 2012. The increase is particularly pronounced in the clouds with highest IWC. These high IWC clouds are associated with significant enhancements in total H2O (vapor and ice). We suggest this implies an additional source of H2O and that this is provided by space traffic exhaust. A preliminary estimate of the H2O released from summertime space traffic over the last six years is qualitatively consistent with this suggestion.